Translumbar type II endoleak embolization with a new liquid iodinated polyvinyl alcohol polymer: Case series and review of current literature - Leati, Giovanni; Di Bartolomeo, Francesco; Maffi, Gabriele; Boccalon, Luca; Diaco, Domenico; Segalini, Edoardo; Spinazzola, Angelo (Frontiers in Radiology, 2023)
Purpose To describe our experience with the use of a novel iodized Polyvinyl Alcohol Polymer liquid agent (Easyx) in type II endoleak treatment with translumbar approach. Methods Our case series is a retrospective review of patients with type II endoleak (T2E) treated with Easyx from December 2017 to December 2020. Indication for treatment was a persistent T2E with an increasing aneurysm sac ≥ 5 mm on computed tomography angiography (CTA) over a 6-month interval. Technical success was defined as the embolisation of the endoleak nidus with reduction or elimination of the T2E on sequent CTA evaluation. Clinical success was defined as an unchanged or decreased aneurysm sac on follow up CTA. Secondary endpoints included the presence of artifacts in the postprocedural cross-sectional tomographic imaging and post and intraprocedural complications. Results Ten patients were included in our retrospective analysis. All T2E were successfully embolized. Clinical success was achieved in 9 out of 10 patients (90%). Mean follow-up was 14 3-20 months. No beam hardening artifact was observed in follow-up CT providing unaltered imaging. Conclusion Easyx is a novel liquid embolic agent with lava-like characteristics and unaltered visibility on subsequent CT examinations. In our initial experience Easyx showed to have all the efficacy requisites to be an embolisation agent for type II EL management. Its efficacy, however, should be evaluated in more extensive studies and eventually compared with other agents.